Placental Stem Cells from Domestic Animals: Translational Potential and Clinical Relevance. Issue 1 (January 2018) - Barboni, B.; Russo, V.; Berardinelli, P.; Mauro, A.; Valbonetti, L.; Sanyal, H.; Canciello, A.; Greco, L.; Muttini, A.; Gatta, V.; Stuppia, L.; Mattioli, M.
The field of regenerative medicine is moving toward clinical practice in veterinary science. In this context, placenta-derived stem cells isolated from domestic animals have covered a dual role, acting both as therapies for patients and as a valuable cell source for translational models. The biological properties of placenta-derived cells, comparable among mammals, make them attractive candidates for therapeutic approaches. In particular, stemness features, low immunogenicity, immunomodulatory activity, multilineage plasticity, and their successful capacity for long-term engraftment in different host tissues after autotransplantation, allo-transplantation, or xenotransplantation have been demonstrated. Their beneficial regenerative effects in domestic animals have been proven using preclinical studies as well as clinical trials starting to define the mechanisms involved. This is, in particular, for amniotic-derived cells that have been thoroughly studied to date. The regenerative role arises from a mutual tissue-specific cell differentiation and from the paracrine secretion of bioactive molecules that ultimately drive crucial repair processes in host tissues (e.g., anti-inflammatory, antifibrotic, angiogenic, and neurogenic factors). The knowledge acquired so far on the mechanisms of placenta-derived stem cells in animal models represent the proof of concept of their successful use in some therapeutic treatments such as for musculoskeletal disorders. In the next future, legislation in veterinary regenerative medicine will be a key element in order to certify those placenta-derived cell-based protocols that have already demonstrated their safety and efficacy using rigorous approaches and to improve the degree of standardization of cell-based treatments among veterinary clinicians.